Body mass index, waist circumference, and waist-hip ratio: which is the better discriminator of cardiovascular disease mortality risk? Evidence from an individual-participant meta-analysis of 82,864 participants from nine cohort studies - Czernichow, Sébastien (2011)
Few studies have examined both the relative magnitude of association and the discriminative capability of multiple indicators of obesity with cardiovascular disease (CVD) mortality risk. We conducted an individual-participant meta-analysis of 9 cohort studies of men and women drawn from the British general population resulted in sample of 82,864 individuals. Body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) were measured directly. There were 6,641 deaths (1,998 CVD) during a mean of 8.1 years of follow-up. After adjustment, a one SD higher in WHR and WC was related to a higher risk of CVD mortality (HR (95% CI)): 1.15 (1.05-1.25) and 1.15 (1.04-1.27), respectively. The risk of CVD also increased linearly across quintiles of both these abdominal obesity markers with a 66% increased risk in the highest quintile of WHR. In age- and sex-adjusted models only, BMI was related to CVD mortality but not in any other analyses. No major differences were revealed in the discrimination capabilities of models with BMI, WC or WHR for cardiovascular or total mortality outcomes. In conclusion, measures of abdominal adiposity, but not BMI, were related to an increased risk of cardiovascular disease mortality. No difference was observed in discrimination capacities between adiposity markers.